2013
DOI: 10.1038/mtna.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

Lipidoid Nanoparticles Containing PD-L1 siRNA Delivered In Vivo Enter Kupffer Cells and Enhance NK and CD8+ T Cell-mediated Hepatic Antiviral Immunity

Abstract: Effective clinical application of antiviral immunotherapies necessitates enhancing the functional state of natural killer (NK) and CD8+ T cells. An important mechanism for the establishment of viral persistence in the liver is the activation of the PD-1/PD-L1 inhibitory pathway. To examine the role of hepatic myeloid PD-L1 expression during viral infection, we determined the magnitude and quality of antiviral immune responses by administering PD-L1 short-interfering RNA (siRNA) encapsulated in lipidoid nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…In the case of viral persistence in the liver, the abrogation of PD-L1 by siRNA was shown to enhance the number of intrahepatic NK cells and CTL, thereby increasing cytotoxicity, cytokine production, viral clearance, and memory (148). During HIV infection, PD-1 levels increase on patient NK cells, and this has been shown to diminish NK cell proliferation (145).…”
Section: Pd-1 or Pd-l1 Blocking Monoclonal Antibodiesmentioning
confidence: 99%
“…In the case of viral persistence in the liver, the abrogation of PD-L1 by siRNA was shown to enhance the number of intrahepatic NK cells and CTL, thereby increasing cytotoxicity, cytokine production, viral clearance, and memory (148). During HIV infection, PD-1 levels increase on patient NK cells, and this has been shown to diminish NK cell proliferation (145).…”
Section: Pd-1 or Pd-l1 Blocking Monoclonal Antibodiesmentioning
confidence: 99%
“…Silencing of Pdl1 effectively enhanced the NK cell and CD8+ T cell intrahepatic accumulation, viral clearance, and CD8+ T cell memory to hepatotropic viral infection. This study demonstrated that transient knockdown of PD-L1 using siRNA directly on the disease-causing cell type might even have benefits when compared to monoclonal antibody usage [158]. …”
Section: Future Prospectsmentioning
confidence: 99%
“…Importantly, KCs contribute to liver Treg cell-derived IL-10 production [20], and HBV particles also induce TGF-β production by KCs and probably promote Treg cell differentiation [50]. Beside IL-10 and TGF-β-mediated liver immune tolerance, activated KCs inhibit liver T cell responses through upregulation of co-inhibitory molecules [18]. By delivering the lipidoid nanoparticles carrying PD-L1 siRNA to KCs in vivo, Dolina et al demonstrated that silence of PD-L1 in KCs during Ad and murine cytomegalovirus (MCMV) infection resulted in enhanced hepatic CD8 T cell accumulation, effector cytokine production, and viral clearance [18].…”
Section: Kupffer Cellsmentioning
confidence: 99%
“…Beside IL-10 and TGF-β-mediated liver immune tolerance, activated KCs inhibit liver T cell responses through upregulation of co-inhibitory molecules [18]. By delivering the lipidoid nanoparticles carrying PD-L1 siRNA to KCs in vivo, Dolina et al demonstrated that silence of PD-L1 in KCs during Ad and murine cytomegalovirus (MCMV) infection resulted in enhanced hepatic CD8 T cell accumulation, effector cytokine production, and viral clearance [18]. It is also reported that PD-1 expression is associated with CD8 T cell exhaustion in acute HCV infection [51].…”
Section: Kupffer Cellsmentioning
confidence: 99%
See 1 more Smart Citation